Waiting to Imitate: On the Dynamic Pricing of Knowledge - Henry, Emeric; Ponce, Carlos J. (Journal of Political Economy, 2011)
We study the problem of an inventor who brings to the market an innovation that can be legally imitated. Imitators may “enter” the market by imitating the innovation at a cost or by buying from the inventor the knowledge necessary to reproduce and use the invention. The possibility of contracting dramatically affects the need for patent protection. Our results show that (i) imitators wait to enter the market and the inventor becomes a temporary monopolist; (ii) the inventor sells knowledge through contracts that allow resale by the imitators; and (iii) under certain conditions, the inventor’s payoff increases with the number of imitators.